PENGARUH KUALITAS PELAYANAN CHECK-IN COUNTER MASKAPAI GARUDA INDONESIA TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA SULTAN BABULLAH TERNATE - Atwal, Sitti Balqis; Laksana, Andityo Pujo (Relawan Jurnal Indonesia, 2022)
The Indonesian airline that carries the idea of ​​a full service airline is Garuda Indonesia (a full service airline). One of the services that passengers experience for the first time when using Garuda Indonesia Airlines services before departure is the check-in (preflight) process. The check-in counter is a self-reporting process regarding the departure of passengers to make a trip. If the check-in counter service is good, passengers will feel satisfied and will not cause accumulation. However, there are still many obstacles experienced by passengers during the check-in process at the departure terminal of Sultan Babullah Ternate Airport causing dissatisfaction with the quality of check-in services (Siti FatmaBuhari, 2020). This study uses quantitative data. And using the data generated from primary data in accordance with the questionnaire distributed to Garuda Indonesia airline passengers at Sultan Babullah Airport Ternate for the period September 2021 and totaling 96 people, using simple linear regression data analysis techniques, T-test, and coefficient of determination. The results of hypothesis testing with the T test stated that the value of tcount 10.450, the value of ttable 1.986 and the results of the Coefficient of Determination test showed how much influence the X variable had on the Y variable, with a value of 53.7% and the remaining 46.3% the cause was other factors not examined by researchers.